Jikonahati : modo de ser e viver Haliti-Paresi na cultura contemporânea - Martins, Elias (2023)
The present production highlights a game practiced by the Haliti-Paresi ethnicity, in which its practice has not been secularized by contemporary sports. Within the sociocultural organization of this ethnic group, Jikonahati expresses knowledge and values that would have allowed indigenous people to engage with non-indigenous structures and knowledge. They learned to use this knowledge in favor of their ethnicity and ways of being and living. We also sought to understand, from our perspective, the knowledge, values, beliefs, as well as the rituals that make up the habitus of this interdependent ball game in the process of forming, constituting, and fostering the Haliti-Paresi ethnic identity. Through bibliographical studies relevant to the context and for use in this qualitative research, we immersed ourselves in the research field. Using participant observation and semi-structured interviews with five leaders from the Quatro Cachoeira village, located in the Utiariti indigenous land in Campo Novo do Parecis, Mato Grosso. In addition to revealing myths, knowledge, and a habitus, the interviewees also engaged in a game with the surrounding society so that Jikonahati represented, in the non-indigenous imaginary, an inclusive contemporary identity. The experiences with professional soccer of one of the interviewees revealed knowledge and values that can be learned. However, learning does not occur organically, as it lacks the corporeality of childhood and adolescence experienced within the Haliti-Paresi ethnic group. We observed that this game goes far beyond a systematized practice with rules and standardized learning models; Jikonahati organized sociocultural life, represented in the knowledge, beliefs, and values of a way of being and living based on the teachings of the mythical leader Wazare, stating that he is the head that commands the body.